"A Shelter Can Tip the Scales Sometimes": Disinvestment, Gentrification, and the Neighborhood Politics of Homelessness in 1980s New York City. (November 2017) - Eisenberg, Ariel
In the 1980s, visible homelessness became one of the most pressing problems in New York City. While most New Yorkers expressed sympathy for the homeless, many of them also resisted efforts to site shelters and service facilities in their neighborhoods. But far from being simply a case of NIMBY (not-in-my-back-yard) sentiment, protests over the placement of these facilities arose in the context of decades-long neighborhood movements against urban disinvestment and the beginning of gentrification in some New York City neighborhoods. I argue that understanding this history is crucial to parsing the complex politics of anti-homeless facility protests in the 1980s and to understanding the rise of "quality of life" policies that would govern many neoliberal urban spaces by the 1990s.